Anthropometric characteristics of children 7 to 12 years old in high altitude and low altitude, a study of growth adaptation in Samigaluh and Galur Districs, Kulon Progo Regency, Yogyakarta Province - Janatin Hastuti, Janatin Hastuti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2005)
Background: Age of 7-12 years is an important periode for childrens growth and development. Some factors affect growth process i.e. internal, external and enviromental factors. Some studies show that high altitude has effects on anthropometric characteristics of children which are reflected on the difference of growth patterns.Objective: The aims of this research were to know the differences of anthropometric characteristics between children living in high altitude and low altitude, and to know the effect of different altitude environtment on the anthropometric characteristics of children.Methods: Investigation was done on 565 children of 7-12 years old, boys and girls, which consisted of 255 children living in Samigaluh (high altitude) and 310 children living in Galur (low altitude). These two districts are located in Kulon Progo Regency in Yogyakarta Province. The anthropometric characteristics of the subjects were the measurements of weight, stature, biacromiale breadth, chest breadth, chest depth, bicristal breadth, upper arm circumference, chest circumference, sum of 4 skinfold thickness (triceps, infrascapular, suprailiac and calf skinfold) and sitting height. Many indices were calculated, i.e. Livi index, trunk height index, acromial index, chest index, bicristal index, acromiocristalis index, chest circumference index and skelic index. Statistical analysis of three ways anova and t-test were performed on the data. Mann-Witney test was conducted to reveal the difference of distribution among the indices category.Results: The results chest breadth, chest depth and sum of 4 skinfold thickness differed significantly between boys and girls of 7-12 years old in each district but there were no differences between children of Samigaluh and Galur. There were significant differences in the measurements of chest depth and chest index between 7-12 years old boys and girls of Samigaluh and Galur.Conclusions: The anthropometric characteristics of children living in different altitude differed in the measurements of chest depth and chest index.Â Key words: anthropometric characteristics - high altitude - low altitude - growthÂ Â